Pessary use in stress urinary incontinence: a review of advantages, complications, patient satisfaction, and quality of life - Al-Shaikh G; Syed S; Osman S; Bogis A; Al-Badr A (Dove Medical Press, 2018)
Ghadeer Al-Shaikh,1 Sadiqa Syed,2 Somaia Osman,3 Abdulrahman Bogis,1 Ahmed Al-Badr31Department of Obstetrics and Gynecology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2Department of Basic Sciences, College of Medicine, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 3Department of Urogynecology & Pelvic Reconstructive Surgery, Women’s Specialized Hospital, King Fahad Medical City, Riyadh, Saudi Arabia Abstract: Stress urinary incontinence (SUI) is a common condition among women. The usual approach to treatment of SUI is a stepwise plan from conservative to surgical procedures. A vaginal pessary is one of the commonly used conservative treatments that offer symptomatic improvement for women with incontinence. This review provides a critical analysis of the benefits and shortcomings offered by vaginal pessaries to patients affected by SUI, with a particular focus on indications, advantages, quality of life, patient satisfaction, and potential complications. To obtain the required information, an extensive search of PubMed and Cochrane databases was performed, covering the time frame from January 2000 to December 2016. We also surveyed the published guidelines of American Urological Association, Canadian Urological Association, American Urogynecological Society, National Institutes of Health (USA), and National Institute for Health and Care Excellence (UK). A total of 192 original research papers, review articles, and clinical trials were identified. The analysis of retrieved data provides evidence that vaginal pessaries constitute an effective nonsurgical option for SUI. The satisfaction rate with pessary use is high and only minor complications, if any, occur, vaginal discharge being the most common. The reviewed studies document that vaginal pessaries provide an adequate control of SUI if they are fit properly and managed by frequent replacements and regular checkups. They should be considered among the first line of treatment for SUI associated with exercise and increased intra-abdominal pressure.Keywords: pessary, urinary incontinence, nonsurgical intervention, vaginal prolapse